M46 - DISCOVERY BIOLOGY OF NEUROPSYCHIATRIC SYNDROMES: A CENTER FOR INTEGRATING CLINICAL MEDICINE AND BASIC SCIENCE (DBNS): INTEGRATING CLINICAL PSYCHIATRY AND BASIC SCIENCE - Jain, Sanjeev; ADBS Consortium (European neuropsychopharmacology, 2019)
Traditional clinical classification systems conceptualize the psychiatric disorders as a group of related disorders or discrete entities syndromes that are supposedly independent of each other. However, there is now accumulating evidence that there exist overlapping genetic, environmental and developmental factors, cutting across these diagnostic boundaries. There is sufficient evidence to suggest that these disease biological processes start long before manifestation being manifest as to a clinically recognizable syndrome. We will establish a registry of 300 multiple affected families in whom multiple members (more than 2 affected in a nuclear family) are diagnosed with major psychiatric disorders (schizophrenia, bipolar disorder, obsessive compulsive disorder, dementias and substance use disorders) with structured assessments and create a unified digital database. We will study brain structural [grey (magnetic resonance imaging-MRI) and white matter (diffusion tensor MRI)] abnormalities, resting and task-related functional MRI activity, neuropsychological performance, brain electrical activity and eye movement abnormalities in probands with major psychiatric disorders and their unaffected first-degree relatives (FDR); in comparison with matched healthy controls. The families will be subjected to a uniform set of clinical analyses; and a bio-repository will be set up using cellular material (lymphocytes, induced pluripotent stem cells, neural stem cells). Whole exome sequencing will be performed We will also examine the time course and progression of brain abnormalities and study their relationship to course of illness and disease conversion. We hypothesize that patients will have significant specific grey matter volume deficits and white matter hypo-connectivity; aberrant neuro-hemodynamic response involving frontal, striatal & limbic brain regions during fMRI; abnormal brain electrical activity and antisaccade/smooth pursuit eye movements; prominent and specific patterns of impairments in verbal memory, verbal fluency, sustained attention and executive functions, in comparison with matched healthy controls. Unaffected relatives will have brain abnormalities that are intermediate between affected subjects and healthy controls. A composite endophenotype comprising of neuroimaging and neurocognitive parameters should be able to differentiate three groups Cellular assays will similarly differentiate cell lines derived from the three groups. Greater brain abnormalities/composite endophenotype measures/cellular abnormalities at baseline will predict poorer course and outcome/ treatment response. The relation between these, and the genetic variations, would be amenable for further analysis, to understand the genotype-phenotype conversion. The DBNS is an enthusiastic thus an ambitious attempt approach to create a database that combines a wealth of clinical data with a comprehensive psychological and biological assessment, over time. clinical-basic science database with on-going biological follow-up of recruited individuals; and a biorepository. The resources generated will hopefully serve as a platform to answer several questions related to the neurobiology of psychiatric disorders; as well as fundamental questions about neuro-development and degeneration.